Expanding the Porphycene Core: Modification and Metalation - Brewster, James T., II; Anguera, Gonzalo; Sessler, Jonathan L. (Synlett, 2019)
Porphycenes, the first structural isomer of porphyrin, display unique chemical and photophysical properties. In this Account, we detail our group’s individual and collaborative efforts in elucidating further the chemical properties of porphycene. Particular emphasis will be placed on recent efforts devoted to expanding the porphycene core.1 Introduction2 Exploring the Chemistry of Porphycene3 Synthesis and Metalation of an Expanded Porphycene4 Conclusion
Keywords: porphyrinoid; expanded porphycenes; coordination chemistry; porphycene materials; porphycene therapeutics; electronic communication; porphycenes; macrocycles; metal complexes; expanded porphyrins; hetero-annulenes